Morphological Diversity of Coffea arabica L. with Yellow, Orange, and Purple Fruit from Temanggung - Aswin Hendry Atmoko; Sri Hartati; Parjanto (Jurusan Agroteknologi, 2026)
Temanggung possesses unique Arabica coffee accessions with yellow, orange, and purple ripe fruits. However, their morphological diversity has not yet been documented using standardized IPGRI descriptors. This study evaluated the morphological diversity of 15 Coffea arabica accessions with distinct fruit color using 29 qualitative morphological characters. The results revealed substantial variation among accessions, Shannon–Wiener diversity index (H′) ranging from 0.000 to 1.679, with an average of 0.721, suggesting overall moderate diversity. Highly variable traits included young leaf color, shoot color, fruit color, fruit shape, and seed shape. While characters such as venation pattern, bud wax color, domatia shape, and inflorescence position were uniform across accessions. Fruit color, the primary distinguishing trait, exhibited high diversity (H′ = 1.552), comprising six distinct categories, with orange being the most dominant. Fruit color showed substantial variation, but no consistent morphological pattern was observed across accessions with different fruit colors. Further genetic and association analyses are needed to clarify the relationship between fruit color and other qualitative traits. Cluster analysis using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) implemented in NTSYSpc version 2.02i grouped the accessions into two major clusters, with one accession forming a distinct cluster, reflecting its unique morphological characteristics. The similarity index ranged from 0.27 to 0.75, indicating moderate to high diversity and the absence of closely identical accessions based on morphological traits. These findings confirm that observed Arabica coffee accessions from Temanggung possess considerable morphological variability, providing a valuable genetic resource for selection and breeding programs. Key words: Arabica coffee, germplasm, local, morphological variation, phenotype ABSTRAK Temanggung memiliki aksesi kopi Arabika yang unik dengan buah matang berwarna kuning, oranye, dan ungu. Namun keragaman morfologinya belum didokumentasikan dengan menggunakan deskriptor berstandar IPGRI. Penelitian ini bertujuan untuk mengevaluasi keragaman morfologi 15 aksesi Coffea arabica dengan warna buah yang berbeda menggunakan 29 karakter morfologi kualitatif. Hasil penelitian menunjukkan variasi morfologi yang cukup besar antar aksesi, dengan indeks keragaman Shannon–Wiener (H′) berkisar antara 0.000–1.679 dan rata-rata 0.721, yang menunjukkan tingkat keragaman sedang. Karakter dengan keragaman tinggi meliputi warna daun muda, warna tunas, warna buah, bentuk buah, dan bentuk biji. Sedangkan, pola venasi daun, warna wax kuncup, bentuk domatia, dan posisi bunga menunjukkan kondisi yang seragam pada seluruh aksesi. Warna buah sebagai karakter pembeda utama memiliki keragaman tinggi (H′ = 1.552) dengan enam kategori warna, didominasi oleh warna oranye. Meskipun demikian, tidak ditemukan pola morfologi yang konsisten pada aksesi dengan warna buah yang berbeda. Oleh karena itu, analisis genetik dan analisis asosiasi masih diperlukan untuk mengklarifikasi hubungan antara warna buah dan karakter morfologi kualitatif lainnya. Analisis klaster menggunakan metode Unweighted Pair Group Method with Arithmetic Mean (UPGMA) dengan aplikasi NTSYSpc versi 2.02i mengelompokkan aksesi menjadi dua klaster besar, dengan satu aksesi membentuk cluster yang berbeda, mencerminkan karakteristik morfologi yang unik. Indeks kemiripan berkisar antara 0.27–0.75, menunjukkan keragaman morfologi sedang hingga tinggi tanpa adanya aksesi yang identik. Temuan ini menegaskan bahwa aksesi kopi Arabika Temanggung memiliki keragaman morfologi yang tinggi dan berpotensi menjadi sumber daya genetik yang penting untuk program seleksi dan pemuliaan. Kata kunci: Fenotip, kopi Arabika, lokal, plasma nutfah, variasi morfologi